Non-Coding RNAs Regulate the Resistance to Anti-EGFR Therapy in Colorectal Cancer - Chu, Jinjin; Fang, Xianzhu; Sun, Zhonghou; Gai, Linlin; Dai, Wenqing; Li, Haibo; Yan, Xinyi; Du, Jinke; Zhang, Lili; Zhao, Lu; Xu, Donghua; Yan, Shushan (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is the third prevalent cancer worldwide, the morbidity and mortality of which have been increasing in recent years. As molecular targeting agents, anti-epidermal growth factor receptor (EGFR) targeted monoclonal antibodies (McAbs) have noticeably increased the progression-free survival (PFS) as well as overall survival (OS) of patients with rat sarcoma viral oncogene (RAS)- and v-raf murine sarcoma viral oncogene homolog B (BRAF)-wild-type metastatic CRC (mCRC). Nevertheless, most patients are eventually resistant to anti-EGFR McAbs. The mechanism of anti-EGFR drug resistance remains unclear. Increasing studies have implicated non-coding RNAs (ncRNAs), which primarily include microRNAs (miRNAs), circular RNAs (circRNAs) and long non-coding RNAs (lncRNAs), are widely involved in tumorigenesis and tumor progression. They function as essential regulators controlling the expression and function of oncogenes. Increasing data has shown ncRNAs affect the resistance of molecular targeted drugs in CRC. In this paper, we have reviewed current progress in the regulatory mechanisms of ncRNAs in anti-EGFR McAbs therapy resistance in CRC. It provides insight into exploring the clinical potentials of ncRNAs as new small molecule targets and prognostic markers for CRC.